2010
DOI: 10.1103/physreve.82.017201
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical effects of integrative time-delay coupling

Abstract: We study coupled dynamical systems wherein the influence of one system on the other is cumulative: coupling signals are integrated over a time interval τ. A major consequence of integrative coupling is that amplitude death occurs over a wider range and in a single region in parameter space. For coupled limit cycle oscillators (the Landau-Stuart model) we obtain an analytic estimate for the boundary of this region while for coupled chaotic Lorenz oscillators numerical results are presented. For given τ we find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…Closely related to the case of distributed delays is the situation where systems respond to cumulative signals, namely by integrating information received over an interval in time. This occurs when systems have a finite intrinsic response time and also causes the region of AD to extend indefinitely [56,57].…”
Section: Delay Interactionmentioning
confidence: 99%
“…Closely related to the case of distributed delays is the situation where systems respond to cumulative signals, namely by integrating information received over an interval in time. This occurs when systems have a finite intrinsic response time and also causes the region of AD to extend indefinitely [56,57].…”
Section: Delay Interactionmentioning
confidence: 99%
“…Very recently Sekikawa and coworkers [47] have explained the sudden transition from chaotic motion to the state of AD, a kind of transition observed earlier [48,24,32] too. The group has done the analysis for Bonhoeffer van der Pol oscillator and have found that such a direct transition to AD is a result of saddle-node bifurcation.…”
Section: Scenariosmentioning
confidence: 99%
“…When the coupling involves transmission delay, AD follows as a natural consequence [16,17]. More realistic situations are modeled by including delays that are not fixed but are distributed in some manner and this is shown to enhance the region of stability in the parameter space [23,24].…”
mentioning
confidence: 99%
“…Since distributed delays cover a broad spectrum of configurations [13,14], for ease of communication we address this particular distribution incorporating response time (rather than considering uncertainty in discrete delay [14]) as 'integrative coupling' [17]. In a recent study [16] we explored the effect of such coupling on bidirectionally coupled systems. In this paper the effect has been investigated for unidirectionally coupled oscillators.…”
Section: Introductionmentioning
confidence: 99%